Pengaruh Employee Empowerment Terhadap Employee’s Performance Bisnis Fashion Syariah - Hapsari, Safira Arsyadin (ITB AAS INDONESIA Surakarta, 2023)
There are many rivals in the sharia fashion business, because of the rise of this sharia fashion business, many people are involved and competing in sharia fashion which is a challenge for those who have this business. With this employee empowerment, it will affect employee performance, because with employees who carry out their jobs correctly can grow employee performance to motivate employees to give their best in carrying out their goals and business. If employees are motivated to provide the best for their business, then employees will be much more familiar with the business and the goals of the organization or business which is also called organizational commitment. A business will also experience inequality, so there needs to be a quality of performance appraisal system which will discuss the evaluation of employee's performance and a business and aims to stay in the business goals. If the Islamic fashion business runs this in its business, then the business will continue to run even the latest innovations